RETROSPECTIVE LOOK AT CHANGE IN BRAIN NATRIURETIC PEPTIDE VALUES IN AMBULATORY PATIENTS WITH CHRONIC HEART FAILURE - Wahla, Wahla AS; Pascual, Pascual R; Rafeq, Rafeq Z; Joseph, Joseph J (Journal of Ayub Medical College Abbottabad, 2012)
Background: There is significant interest in the role of B-type natriuretic peptide (BNP) guided therapy for outpatient congestive heart failure (CHF) patients. The objective of this study was to see if the percentage change in BNP levels can predict CHF hospitalisations or death. Methods: We retrospectively reviewed the records of CHF patients who had BNP levels drawn on two clinic visits. Patients were divided into two groups, those with a 70% or greater increase in the BNP values and those in whom the BNP value either decreased or did not increase by 70%. Primary outcome measured was the need for hospitalisation for CHF or death within 6 months of the second clinic visit. Results: One hundred and fourteen (114) paired BNP measurements were included in the analysis. Of these, 26 had >70% increase in BNP while 88 did not. Hospitalisations for CHF or death at 6 months were significantly higher in the former group than the latter (p=0.04). On multivariate regression analysis significant change in BNP remained a predictor of adverse outcomes. Conclusions: In stable outpatients with CHF, >70% increase in BNP is an independent risk factor for CHF hospitalisations or death at 6 months. Keywords: Congestive heart failure, B-type natriuretic peptide, outpatient, hospitalisation